PENGEMBANGAN INSTRUMEN TES PEMAHAMAN KONSEP PADA MATERI POKOK GETARAN DAN GELOMBANG TINGKAT SEKOLAH MENENGAH PERTAMA - Putri, Maulana; Fakhruddin, Fakhruddin; Sahal, Muhammad (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: The learning device developed in this research was a physics learning tool in the form of a concept understanding test instrument. The purpose of this research is to produce a valid concept understanding instrument on the material of vibrations and waves. This research is expected to be a reference in making a valid test instruments, especially on the vibrations and waves material. The type of research is Research and Development (R & D) by using the ADDIE Model. However, this research is only limited to the development stage. The research instrument was used a validation assessment sheet for the Concept Understanding Test Instrument used by the validator to assess learning devices. The analysis data for this research was used descriptive analysis by calculating the validity score of each indicator of the learning devices. The results showed that the Concept Understanding Test Instrument was declared valid with the overall percentage of the device is 83.75% in the Very High category. So that it was declared acceptable for use in learning to test the level of conceptual understanding on the subject matter of vibrations and waves in class VIII of Junior High School.Key Words: Test instrumen of concept understanding, ADDIE model, vibrations and waves.